Effect of Vermicompost on Growth and Yield pf Okra (Abelmoschus esculentus L. cv. Barista) Under Different Mulch Conditions at Chitwan, Nepal - Sapkota, Bigya; Lamsal, Ganesh; Adhikari, Raj Kumar (Journal of the Institute of Agriculture and Animal Science, 2024)
Okra (Abelmoschus esculentus L.) is one of the popular vegetables in Nepal which holds a significant health and nutritional value. To address major bottleneck for lower productivity of okra mainly due to inadequate nutrient management, weed management and soil moisture management, an experiment was conducted at Chitwan, Nepal during March to June 2023 to assess the effects of vermicompost on growth and yield of okra under different mulch conditions. The experiment was laid out in two factorial RCBD design with three replications. Factor A comprised of vermicompost (control, 5t/ha, 10t/ha, 15t/ha, 20t/ha) and factor B was mulching conditions (No Mulch and Plastic Mulch). The collected data were tabulated in Microsoft Excel and analyzed using R Stat version 4.3.1. Means were separated using Duncan’s Multiple Range Test (DMRT) at a significance level of 5%. The results revealed that the effect of vermicompost was significant on most of the growth and yield parameters in mulched conditions. The yield parameters like fruit length (12.37cm), average fruit weight (17.97g), fruit diameter (17.78mm), number of fruits per plant (25.64), yield per plant (426.47g) and yield per hectare (14.83t/ha) were significantly higher under 20t/ha vermicompost. Similarly, the yield parameters like fruit length (12.37cm), average fruit weight (18.02g), fruit diameter(17.82mm), number of fruits per plant (28.73), yield per plant (478.84g), yield per hectare (16.62t/ha) were significantly higher in plastic mulch. The interaction effect indicated that the number of fruits per plant (33.45), yield per plant (530.93g) and yield per hectare (18.62 t/ha) were significantly high in the treatment 20t/ha vermicompost under plastic mulch, and 15t/ha vermicompost and plastic mulch. So, based on this study, combining plastic mulch with vermicompost at 15t/ha could be the most fruitful strategy for farmers among different treatments administered in the study.